2015
DOI: 10.1007/s12664-015-0572-5
|View full text |Cite
|
Sign up to set email alerts
|

Serum ferritin levels predict histological severity in patients with nonalcoholic fatty liver disease in India

Abstract: Serum ferritin was low in Indian individuals, and levels even within apparently normal range indicated fibrosis and cirrhosis. A cutoff level of 48.0 IU/mL distinguished fibrosis in NAFLD. Fibroscan correlated well with serum ferritin levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…The best cutoff value of serum ferritin was found to be 51.95 ng/mL, for predicting the occurrence of fibrosis on top of NAFLD in the current study, with a 65% sensitivity and a 60% specificity with AUC 0.658. Similarly, Parikh et al . found that the cutoff value of 48 ng/mL was the best to predict fibrosis in NAFLD with AUC 0.779.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The best cutoff value of serum ferritin was found to be 51.95 ng/mL, for predicting the occurrence of fibrosis on top of NAFLD in the current study, with a 65% sensitivity and a 60% specificity with AUC 0.658. Similarly, Parikh et al . found that the cutoff value of 48 ng/mL was the best to predict fibrosis in NAFLD with AUC 0.779.…”
Section: Discussionmentioning
confidence: 89%
“…The best cutoff value of serum ferritin was found to be 51.95 ng/mL, for predicting the occurrence of fibrosis on top of NAFLD in the current study, with a 65% sensitivity and a 60% specificity with AUC 0.658. Similarly, Parikh et al 35 found that the cutoff value of 48 ng/mL was the best to predict fibrosis in NAFLD with AUC 0.779. On the other hand, Manousou et al 8 found that the cutoff value of serum ferritin 240 ng/mL or more combined with BMI >28.2 identified patients at risk of developing fibrosis with an 82% sensitivity and a 79% specificity.…”
Section: Discussionmentioning
confidence: 89%
“…A wide range of indirect and direct inflammatory parameters were found to be significantly higher in NAFLD or NASH patients when compared with control subjects (e.g., aspartate aminotransferase, thioredoxin, C-reactive protein, α-2-macroglobulin, ceruloplasmin, malondialdehyde, hepatic 8-oxodG, nitric oxide, interleukin-6, interleukin-8, and tumor necrosis factor-α). Most studies also found ferritin levels to be significantly higher in NASH patients compared with control subjects and/or patients with HS and NAFLD patients compared with control subjects 27,36,37,42,[45][46][47][48][49] (►Supplementary Table S2 [online only]). Most of the studies showed no signs of biochemical or histological iron overload to explain the higher ferritin levels.…”
Section: Hyperferritinemia Related To Inflammationmentioning
confidence: 99%
“…4 b). In such patients, hyperferritinemia is an indicator of more advanced fibrosis or accelerated disease progression [46] . However, studies on the effects of phlebotomy have revealed conflicting results, where initial findings that therapeutic venesection improves insulin sensitivity have not been reproduced more recently [47] .…”
Section: Evaluation Of Patients With Suspected Iron Overload Hyperfermentioning
confidence: 99%